Treatment with prothrombin complex concentrate to enable emergency lumbar puncture in patients receiving vitamin K antagonists - Laible, Mona; Beynon, Christopher; Sander, Peter; Purrucker, Jan; Müller, Oliver J.; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Rizos, Timolaos (Annals of emergency medicine, 2016)
Study objective Lumbar punctures are frequently necessary in neurologic emergencies, but effective oral anticoagulation with vitamin K antagonists represents a contraindication. We report the effectiveness of prothrombin complex concentrates to reverse vitamin K antagonist to enable emergency lumbar punctures, as well as evaluate lumbar puncture- and prothrombin complex concentrates-related complications. Methods Consecutive patients treated with prothrombin complex concentrates between December 2004 and June 2014 to enable emergency lumbar puncture were included. International normalized ratio (INR) before and after prothrombin complex concentrates treatment and the time between start of reversal treatment and lumbar puncture were recorded. A target INR of less than or equal to 1.5 was defined as effective prothrombin complex concentrates treatment. Bleeding events, thromboembolic events, and allergic reactions after prothrombin complex concentrates treatment were identified and classified as “related,” “probably,” “possibly,” “unlikely related,” or “not related” to the lumbar puncture and prothrombin complex concentrates infusion. Results Thirty-seven patients were included (64.9% men; median age 76.0 years; interquartile range [IQR] 71.0 to 84.0 years). The intervention with prothrombin complex concentrates was effective in 33 of 37 patients (89.2%; 95% confidence interval [CI], 78.4% to 97.3%). The median INR was 2.2 (IQR 1.8 to 2.9; 95% CI, 1.9 to 2.5) before and 1.3 (IQR 1.2 to 1.4; 95% CI, 1.2 to 1.3) after prothrombin complex concentrates treatment. The median time between start of prothrombin complex concentrates treatment and lumbar puncture was 135 minutes (IQR 76 to 266 minutes; 95% CI, 84 to 198 minutes). One clinically irrelevant intracranial subdural hematoma “related” to the lumbar puncture developed. No allergic reaction was observed, but 2 of 37 patients (5.4%; 95% CI, 0% to 13.5%) experienced a thromboembolic event (1 ischemic stroke, classified “unlikely related,” and 1 myocardial infarction, “possibly related” to prothrombin complex concentrates treatment). Conclusion Reversing the effect of vitamin K antagonist with prothrombin complex concentrates to enable emergency lumbar puncture appears effective and safe, particularly in regard to bleeding events.